The biological relevance of the FspTF transcription factor, homologous of Bqt4, in Fusarium sp. associated with the ambrosia beetle Xylosandrus morigerus - Carreras-Villaseñor, Nohemí; Martínez-Rodríguez, Luis A.; Ibarra-Laclette, Enrique; Monribot-Villanueva, Juan L.; Rodríguez-Haas, Benjamín; Guerrero-Analco, José A.; Sánchez-Rangel, Diana (Frontiers in Microbiology, 2023)
Transcription factors in phytopathogenic fungi are key players due to their gene expression regulation leading to fungal growth and pathogenicity. The KilA-N family encompasses transcription factors unique to fungi, and the Bqt4 subfamily is included in it and is poorly understood in filamentous fungi. In this study, we evaluated the role in growth and pathogenesis of the homologous of Bqt4, FspTF, in Fusarium sp. isolated from the ambrosia beetle Xylosandrus morigerus through the characterization of a CRISPR/Cas9 edited strain in Fsptf. The phenotypic analysis revealed that TF65-6, the edited strain, modified its mycelia growth and conidia production, exhibited affectation in mycelia and culture pigmentation, and in the response to certain stress conditions. In addition, the plant infection process was compromised. Untargeted metabolomic and transcriptomic analysis, clearly showed that FspTF may regulate secondary metabolism, transmembrane transport, virulence, and diverse metabolic pathways such as lipid metabolism, and signal transduction. These data highlight for the first time the biological relevance of an orthologue of Bqt4 in Fusarium sp. associated with an ambrosia beetle.